Ecological factor in the formation of a health-oriented economy (Economics and region, 2022)
The article is devoted to the analysis and discussion of persistent trends in the deterioration of the state of health and the reduction of the life expectancy of the population of Ukraine from the standpoint of the hypothesis of their ecological determinism, as well as the search for mechanisms for the formation of a health-oriented economy in Ukraine, taking into account the environmental factor. The ecological factor is presented as a system of interconnected natural and anthropogenic objective phenomena in which people work, study, live and rest; it consists of the environment, the quality of the working environment and living conditions. Each component of the environmental factor in Ukraine was analyzed. It was determined that the negative consequences of the influence of the environmental factor on people's health are caused by the imperfection of institutional support, the inefficiency of existing institutions, and the social irresponsibility of market subjects – the state, employers, and individuals. The social irresponsibility of the state is manifested in the absence of a consistent policy in the field of environmental protection: lack of environmental standards and audit of their implementation, the problem of waste disposal; lack of effective mechanisms for state regulation of land use and soil protection against erosion; social irresponsibility of employers – dumping dirty water without treatment into water reservoirs, creating unauthorized landfills, violating legislation in the handling of hazardous waste, non-compliance with the technological and sanitary regime of food production at food enterprises, which leads to food poisoning caused by the causative agent of botulism; households show low activity in the field of ensuring the quality of the ecological aspect of everyday life. The need for the formation of an effective institutional environment as a result of the interaction of market subjects, taking into account the environmental factor – a health-oriented economy, is substantiated. Tools are proposed that form a health-oriented economy taking into account the environmental health risk factor; their application institutionalizes the social responsibility of each market entity: it neutralizes the negative impact of the environmental factor on the health of the population and strengthens the positive one.
Keywords: demographic crisis; environmental factor; health; health-oriented economy; institutionalization